THE USE OF GAMES IN SOCIOLOGY CLASSES - Freitas, Estela Sabrina de; Queiroz, Mayra Prachedes; Carvalho, Celia Regina de (Univ Federal Mato Grosso Sul, 2022)
The use of games in Sociology classes is a practice that contributes to the intellectual development of High School students and, therefore, should have space in pedagogical practices. The present study aims at understanding how games and applications might help in the construction of knowledge of Sociology contents. The bibliographical survey was carried out based on several studies related to games, PRADO (2018); CRUZ (2021); teaching of Sociology, FRAGA, LAGE (2003); BNCC [National Common Curricular Basis of Brazil] (2018); AZEVEDO, NASCIMENTOS (2015); and the contributions of ICT in education, SANTOS (2019). This Study has a qualitative nature, and the data were obtained through a proposal of pedagogical intervention relating to the implementation of two versions of the same game - one as a boardgame and the other in the Kahoot applicative - as well as a survey on the Google Forms platform made available to a group of High School students from a state school located in the city of Curitiba - State of Parana. The data collected were dully analyzed through impressions during the usage of games and according to the statements of students reported in the survey. Thus, we were able to understand that the games contributed to the learning of Sociology contents, making the class more dynamic, and the learning more pleasant, as well as assuring wider interaction and participation in the proposed activities. It is therefore understood that the pedagogical practices need to be updated, taking into account the technological tools that are part of the daily routine of many students, bringing a myriad of innovative possibilities that are available in education to the process of knowledge construction.
Keywords: Pedagogical Practice; Learning; High School